Welcome! Check out our free B-School Guides to learn how you compare with other applicants.

## Is x > 0?

This topic has 2 expert replies and 5 member replies
PGMAT Rising GMAT Star
Joined
23 Jul 2010
Posted:
73 messages
Is x > 0? Fri May 04, 2012 7:45 am
Elapsed Time: 00:00
• Lap #[LAPCOUNT] ([LAPTIME])
Is x > 0?

(1) |x + 3| = 4x - 3
(2) |x - 3| = |2x - 3|

Need free GMAT or MBA advice from an expert? Register for Beat The GMAT now and post your question in these forums!

### GMAT/MBA Expert

Mike@Magoosh GMAT Instructor
Joined
28 Dec 2011
Posted:
398 messages
Followed by:
57 members
Thanked:
236 times
Fri May 04, 2012 5:01 pm
Hi, there. I'm happy to help with this.

First of all, a review. If A and B are algebraic expressions, then the first step of solving
|A| = B
is to say
A = B or A = -B.
(BTW, the word "or" is an important piece of mathematical equipment; it's not garnish!)
Also, with absolute value equations, you always have to check your answers, because the algebraic approach can result in extraneous roots.

Prompt: Is x > 0?
Statement #1: |x + 3| = 4x - 3

We get:
x + 3 = 4x - 3 or x + 3 = -(4x - 3)
x + 3 = 4x - 3 or x + 3 = -4x + 3
6 = 3x or 5x = 0
x = 2 or x = 0

Check both:
|2 + 3| = 5
4(2) - 3 = 5 -----> x = 2 is a solution

|0 + 3| = 3
4(0) - 3 = -3 -----> x = 0 doesn't work: it's an extraneous solution.

Thus, statement #1 leads to the unambiguous answer of x = 2, so we know that x > 0. Statement #2, by itself, is sufficient.

Statement #2: |x - 3| = |2x - 3|

We get:
x - 3 = 2x - 3 or x - 3 = -(2x - 3)
x - 3 = 2x - 3 or x - 3 = -2x + 3
x = 0 or 3x = 6
x = 0 or x = 2

|0 - 3| = 3
{2(0) - 3| = 3 -----> x = 0 works
|2 - 3| = 1
|2(2) - 3| = 1 -----> x = 2 works

This statement allows for two possible answers for x --- for one of them, x is > 0, and for the other it isn't. Therefore, this statement does not allows us to formulate a definitive answer to the prompt question. By itself, this statement is insufficient.

Does all this make sense?

Here's a related DS for further practice.
http://gmat.magoosh.com/questions/966
When you submit your answer to that question, the next page will have the video explanation.

Let me know if you have any questions.

Mike

_________________
Magoosh GMAT Instructor
http://gmat.magoosh.com/

Thanked by: PGMAT, ritzzzr
sanju09 GMAT Instructor
Joined
21 Jan 2009
Posted:
3262 messages
Followed by:
48 members
Thanked:
190 times
GMAT Score:
760
Sat May 05, 2012 2:30 am
Superb Mike@Magoosh!!

_________________
The laws of nature are but the mathematical thoughts of God. ~Euclid

ronnie1985 GMAT Destroyer!
Joined
23 Dec 2011
Posted:
626 messages
Followed by:
9 members
Thanked:
29 times
Test Date:
June
Target GMAT Score:
750
Sat May 05, 2012 7:41 am
Thank you... Need to do more practice in mod problems

_________________

CharuB Just gettin' started!
Joined
01 Oct 2011
Posted:
2 messages
Tue Oct 09, 2012 2:32 pm
Hi,

I have a little confusion regarding Absolute values.

In the question Statement#2 has absolute values on both the sides,So would it be correct if i say we get:
x - 3 = 2x - 3 or -(x - 3) = -(2x - 3)
Please correct me if i am wrong.

kindly let me know if the correct answer to the question would be choice(E).

Thank you.

### GMAT/MBA Expert

Whitney Garner GMAT Instructor
Joined
21 Sep 2010
Posted:
271 messages
Followed by:
66 members
Thanked:
135 times
GMAT Score:
770
Tue Oct 09, 2012 2:45 pm
CharuB wrote:
Hi,

I have a little confusion regarding Absolute values.

In the question Statement#2 has absolute values on both the sides,So would it be correct if i say we get:
x - 3 = 2x - 3 or -(x - 3) = -(2x - 3)
Please correct me if i am wrong.

kindly let me know if the correct answer to the question would be choice(E).

Thank you.
Hi CharuB!

I can definitely sympathize with the temptations to do that, but there are actually 4 cases we would have to consider (because the expression on the right could be +/- and the expression on the left could be +/- and they don't have to be - or + at the same time. So technically, it could be any of the following:

x - 3 = 2x - 3
-(x - 3) = -(2x - 3)
-(x - 3) = 2x - 3
x - 3 = -(2x - 3)

BUT - notice that some of these are actually identical:

x - 3 = 2x - 3
-(x - 3) = -(2x - 3)
All we have done is multiply both sides by a -1, so they are the same equations!

-(x - 3) = 2x - 3
x - 3 = -(2x - 3)
And again, all we have done is multiply both sides by a -1, so they are the same equations!

So technically, to solve we just need to examine 2 cases:
x - 3 = 2x - 3
x - 3 = -(2x - 3)

Hope that clears up the question!

Whit

_________________
Whitney Garner
GMAT Instructor & Instructor Developer
Manhattan Prep

Contributor to Beat The GMAT!

Math is a lot like love - a simple idea that can easily get complicated

Thanked by: ritzzzr, CharuB
Free Manhattan GMAT online events - The first class of every online Manhattan GMAT course is free. Classes start every week.
CharuB Just gettin' started!
Joined
01 Oct 2011
Posted:
2 messages
Mon Oct 15, 2012 11:56 am
Thanks Whitney.

vikram4689 GMAT Titan
Joined
01 Nov 2009
Posted:
1324 messages
Followed by:
13 members
Thanked:
99 times
Mon Oct 15, 2012 10:37 pm
trick here is whenever we have single || then we have to put the value of variable back in equation and see whether our solution satisfies the equation but for double || cases, we don't have to check by putting value in equation. whatever we found by solving the equations will eventually be solution.

both i) and ii) give x=0,2 but x=0 does not satisfy i) so x=2>0 is proved. for ii) x=0,2 hence insuff.

_________________
Premise: If you like my post
Conclusion : Press the Thanks Button

### Best Conversation Starters

1 vipulgoyal 32 topics
2 hemant_rajput 23 topics
3 guerrero 18 topics
4 abhirup1711 17 topics
5 sana.noor 16 topics
See More Top Beat The GMAT Members...

### Most Active Experts

1 Brent@GMATPrepNow

GMAT Prep Now Teacher

211 posts
2 GMATGuruNY

The Princeton Review Teacher

137 posts
3 Jim@StratusPrep

Stratus Prep

60 posts